Adherence of Candida albicans to silicone is promoted by the human salivary protein SPLUNC2/PSP/BPIFA2. (8th February 2014) - Holmes, A.R.; Rodrigues, E.; van der, P.; Lyons, K.M.; Haigh, B.J.; Wheeler, T.T.; Dawes, P.J.D.; Cannon, R.D.
Summary Interactions between Candida albicans, saliva and saliva‐coated oral surfaces are initial events in the colonization of the oral cavity by this commensal yeast, which can cause oral diseases such as candidiasis and denture stomatitis. Candida albicans also colonizes silicone voice prostheses, and the microbial biofilm formed can impair valve function, necessitating frequent prosthesis replacement. We have previously shown that saliva promoted binding of C. albicans cells to silicone in vitro, and that the selective binding of specific salivary proteins to voice prosthesis silicone mediated attachment of C. albicans cells. The C. albicans cells adhered to a polypeptide (or polypeptides) of 36 kDa eluted from saliva‐treated silicone. We show here that a protein of similar size was identified in replicate blots of the eluate from saliva‐treated silicone when the blots were probed with antibodies to human SPLUNC2, a salivary protein with reported microbial agglutination properties. In addition, SPLUNC2 was depleted from saliva that had been incubated with silicone coupons. To determine whether SPLUNC2 is a yeast‐binding protein, SPLUNC2 cDNA was expressed in Escherichia coli. Purified recombinant His‐tagged protein (SPLUNC2r) bound to silicone as demonstrated by immunoblot analysis of an eluate from SPLUNC2r‐treated silicone coupons and 35S‐radiolabelled C. albicans cells adhered in a dose‐dependent manner to SPLUNC2r‐coated silicone. We conclude that SPLUNC2 binds to silicone and acts as a receptor for C. albicans adherence to, and subsequent colonization of, voice prosthesis silicone.